Alienação parental: a responsabilidade por violação aos princípios do direito de família - Cézar, Janine Paula Guimarães Calmon (2016)
Contemporary society diversity comprises several changes which affect historical, cultural, religious and ideological aspects, as well as different areas of knowledge, with higher impact on Family Law, due to the new arrangements and the plurality of family forms which materialize over time. Given the complexity of family forms, new judicial values have been highlighted, such as affection, tenderness, caring, solidarity and family interaction, in order to protect the plurality of family forms, with the recognition of coexistence based on affection (socio affective relationships), therefore putting an end to the patriarchal family paradigm. New family forms have given rise to controversy in Family Law regarding the inadequacy of the law, mainly concerning liability for parental alienation. Socio affective reality, as perceived in Brazil at present, must be studied from a civil and constitutional law perspective, overcoming prejudicial dogma and granting parents the right of daily interaction with their children, as well as responsible parenting, always seeking the child’s best interest, eliminating selfish and manipulative attitudes or other behaviors which could violate the rights of those involved in parental alienation. Law 12.318/2010 (article 2) defines parental alienation and its many forms. Not only parents but any relative who perceives him/herself as victim of parental alienation can bring legal proceedings against an alienating parent or guardian. The present research intends to demonstrate that the rule should also reach relatives or kin,, adopting parents and children and also situations in which the elderly, who are sometimes as vulnerable as children, are affected by this devastating practice. The application of principles found in the constitution and in other laws has proved to be an effective instrument against the practice of parental alienation, as well as the compulsory implementation of shared custody and other sanctions of pedagogical, reparatory and punitive nature. Parental alienation is, therefore, common practice and can take place in a number of family environments, which makes its understanding, identification and communication to judiciary agents a matter of the utmost importance, so as to ensure that the appropriate action is taken